2015
DOI: 10.1007/s00253-015-6462-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bioaugmentation in para-nitrophenol-contaminated soil on the abundance and community structure of ammonia-oxidizing bacteria and archaea

Abstract: Pseudomonas sp. strain WBC-3 mineralizes the priority pollutant para-nitrophenol (PNP) and releases nitrite (NO 2 − ), which is probably involved in the nitrification. In this study, the rate of PNP removal in soil bioaugmented with strain WBC-3 was more accelerated with more NO 2 − accumulation than in uninoculated soils. Strain WBC-3 survived well and remained stable throughout the entire period. Realtime polymerase chain reaction (real-time PCR) indicated a higher abundance of ammonia-oxidizing bacteria (AO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Aerobic ammonia oxidizers were considered to be an excellent model organism for studying microbial biogeography, due to their functional, numerical, and ecological importance, and the relative ease of characterization (Yao et al, 2013 ). A range of biotic and abiotic factors were distinguished to influence the ecological niches of ammonia oxidizers in upland soils, such as soil pH (Gubry-Rangin et al, 2011 ; Hu et al, 2013a ; Oton et al, 2015 ), soil type (Chen et al, 2010 ), moisture contents (Hu et al, 2015b ), temperature (Tourna et al, 2008 ), C/N ratios (Bates et al, 2011 ), sulfide (Erguder et al, 2009 ), and geographical distance (Hu et al, 2014a ), however, relatively less effort was devoted to decipher the large-scale distribution patterns of ammonia oxidizers in paddy ecosystems. Simultaneously, numerous studies have demonstrated the cellular, genomic, and physiological differences between AOA and AOB (He et al, 2012 ; Prosser and Nicol, 2012 ), and their divergent nitrification pathways and responses to environmental and climatic factors (Tourna et al, 2008 ; Yao et al, 2013 ), which might lead to differential biogeographic patterns between AOA and AOB in paddy soils.…”
Section: Introductionmentioning
confidence: 99%
“…Aerobic ammonia oxidizers were considered to be an excellent model organism for studying microbial biogeography, due to their functional, numerical, and ecological importance, and the relative ease of characterization (Yao et al, 2013 ). A range of biotic and abiotic factors were distinguished to influence the ecological niches of ammonia oxidizers in upland soils, such as soil pH (Gubry-Rangin et al, 2011 ; Hu et al, 2013a ; Oton et al, 2015 ), soil type (Chen et al, 2010 ), moisture contents (Hu et al, 2015b ), temperature (Tourna et al, 2008 ), C/N ratios (Bates et al, 2011 ), sulfide (Erguder et al, 2009 ), and geographical distance (Hu et al, 2014a ), however, relatively less effort was devoted to decipher the large-scale distribution patterns of ammonia oxidizers in paddy ecosystems. Simultaneously, numerous studies have demonstrated the cellular, genomic, and physiological differences between AOA and AOB (He et al, 2012 ; Prosser and Nicol, 2012 ), and their divergent nitrification pathways and responses to environmental and climatic factors (Tourna et al, 2008 ; Yao et al, 2013 ), which might lead to differential biogeographic patterns between AOA and AOB in paddy soils.…”
Section: Introductionmentioning
confidence: 99%
“…TN and TP in the sediment were first digested with sulfuric acid/perchloric acid and then measured via spectrophotometry. The inorganic nitrogen content of the sediment samples was analyzed using the standard methods with some modifications, as described by Chi et al (2015). Briefly, NO 3 -N and NH 3 -N were extracted with 2 M KCl and shaken for 1 hour at 30 °C and shaken at 150 rpm in a shaker.…”
Section: Sampling and Analysismentioning
confidence: 99%